Discording through food. Chinese descendants and new immigrants in Tapachula, Chiapas - LISBONA GUILLÉN, MIGUEL (2022)
In the capital of the coast of Chiapas (Mexico), Tapachula, the arrival of new Chinese immigrants, during the current century, to open restaurant businesses coincides with the presence of similar businesses run by descendants of the historical Chinese immigration to the region. This immigration occurred mainly at the beginning of the 20th century. Through the work carried out for more than a decade, and by means of participant observation and interviews, the article shows how the social representations around the food offered in the city’s businesses establish a clear differentiation between the historical and new gastronomic businesses. Dissociation, in this case, that questions the homogeneous discourses on identity and the territorial and national referents that construct it. Thus, Chinese food is legitimized because it originates in a historical and family heritage of Chinese descendants, and is degraded when it is brought by new immigrants who have recently arrived in Tapachula.